2017
DOI: 10.1111/bjh.14889
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of health‐related quality of life in patients with AL amyloidosis: associations with health outcomes over time

Abstract: SummaryLight chain (AL) amyloidosis is a rare disease associated with significant, irreversible organ dysfunction and high case fatality. An observational study was conducted to assess health‐related quality of life (HRQoL) in patients treated for AL amyloidosis between 1994 and 2014 with both high dose melphalan and stem cell transplantation (HDM/SCT) or non‐SCT chemotherapy regimens. The SF‐36v1® Health Survey (SF‐36) was administered to assess HRQoL during clinic visits. Analysis of variance was used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…Our results show that baseline PROs can be helpful in predicting 1-year (early) mortality in AL amyloidosis even after adjusting for stage at diagnosis. The Boston University Amyloid Center has previously shown health-related quality of life to be of prognostic value with worse pre-treatment physical component scores on the SF-36 associated with a greater risk of mortality in patients who received transplant or non-transplant chemotherapy 20 , 21 . These analyses have shown that the pre-treatment physical component score of the SF-36 can predict post-treatment mortality after adjusting for the number of organs affected 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that baseline PROs can be helpful in predicting 1-year (early) mortality in AL amyloidosis even after adjusting for stage at diagnosis. The Boston University Amyloid Center has previously shown health-related quality of life to be of prognostic value with worse pre-treatment physical component scores on the SF-36 associated with a greater risk of mortality in patients who received transplant or non-transplant chemotherapy 20 , 21 . These analyses have shown that the pre-treatment physical component score of the SF-36 can predict post-treatment mortality after adjusting for the number of organs affected 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The Boston University Amyloid Center has previously shown health-related quality of life to be of prognostic value with worse pre-treatment physical component scores on the SF-36 associated with a greater risk of mortality in patients who received transplant or non-transplant chemotherapy 20 , 21 . These analyses have shown that the pre-treatment physical component score of the SF-36 can predict post-treatment mortality after adjusting for the number of organs affected 21 . Similarly, the Mayo Clinic has shown that a 3-question screen of patient-reported fatigue, pain, and quality of life can be useful in AL amyloidosis with fatigue independently predicting survival in addition to stage and transplant status 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative symptom management with rehabilitation physicians and/or palliative medicine teams might also be of value. In one observational study 176 , significant improvements in vitality, social functioning, role-emotional and mental health were demonstrated after HDM/SCT in patients with AL amyloidosis 176 . Lower pre-treatment SF-36 physical component scores were associated with a greater risk of mortality in patients receiving HDM/SCT or those who received non-SCT chemotherapy regiments and during follow-up periods 176 .…”
Section: [H2] Amyloid Directed Immunotherapymentioning
confidence: 99%
“…In one observational study 176 , significant improvements in vitality, social functioning, role-emotional and mental health were demonstrated after HDM/SCT in patients with AL amyloidosis 176 . Lower pre-treatment SF-36 physical component scores were associated with a greater risk of mortality in patients receiving HDM/SCT or those who received non-SCT chemotherapy regiments and during follow-up periods 176 . An improvement in SF-36 scores after HDM/SCT was also demonstrated in another observational study 99 ; mental component summary scores reached the population norm 1 year post-SCT and physical component summary score reached the population norm 2 years post-SCT.…”
Section: [H2] Amyloid Directed Immunotherapymentioning
confidence: 99%
“…Following treatment, SF-36 scores improved; MCS reached the population norm 1-year post HDM-SCT and PCS reached the population norm 2 years post HDM-SCT [34]. Levels of cardiac biomarkers (NT-proBNP) correlated with mean SF-36 score; an association between risk of death and baseline SF-36 PCS scores has also been shown [35]. SF-36 scores were informative when examining factors associated with early post-treatment survival and subsequent survival beyond 1-year follow-up.…”
Section: Burden Of Illness: Detecting Clinically Meaningful Impacts Omentioning
confidence: 87%